Foreign Investments - A Factor of Economic Development - Akhmedova Dilnoza Habibullaevna, Khairullayev Shahboz Orifjonovich (European Science Publishing, 2023)
The article shows the content of foreign investments, forms of attraction, their role in the development of the economy of Uzbekistan, offers and recommendations aimed at creating a favorable investment environment, as well as active attraction of foreign investments.
Keywords: Investment, foreign investment, innovation, investment climate, foreign direct investments, enterprises with foreign investment, investor.